PHYSICAL BASIS OF STRUCTURAL STRENGTHENING (HEAVY) OF CONCRETE UNDER AXIAL LOCAL COMPRESSION - and and (Municipal economy of cities. Series: «Economy science», 2013)
According to the analysis of physics of the process of hardening of heavy concrete with local compression is well-studied experimentally over the past 80 years, the proposed physical model and method for the quantitative determination of hardening coefficient bj structural concrete under axial compression in the local framework of the developed theory V.N.Rudakovym slip mikropolyarizovannoy environment simple static loading.